The reality of the practice of serving leadership dimensions among the heads of the scientific departments at the University of Hafr al-Batin from the point of view of the faculty members of the university - Al-Shamri, Radhi Ben Turki (Journal of Educational and Psychological Sciences, 2019)
The aim of the research was to investigate the reality of the practice of the dimensions of the servant leadership in the heads of the scientific departments at the University of Hafr Al-Batin. The researcher used the descriptive approach. The tool was in a questionnaire to measure the degree of practice, which was applied to 131 of 600 faculty members Hafr al-Batin with 21.83% of faculty members. The most important results of this study were the following: - The general arithmetic mean for all fields of study reached (3.70) out of (5). This means that the faculty members confirm that the degree of the heads of the departments for the leadership of the servant is high. - that all the terms of the leadership command contained in the questionnaire came at a high and medium level, and finally did not get any of the resolution of the degree of very high, low or very low. - The ranking of the dimensions of the servant leadership according to the degree of the practice of the heads of departments from the point of view of the faculty members ranked in descending order according to the values ​​of the arithmetic averages. It came first after the conceptual skills with an average of 3.76 and came second after empowerment with an average of 3.70. In the third place after the attention to subordinates first with an average (3.65). - There were statistically significant differences in the sex variable at (0.01) in favor of males, and there were no significant differences in the scientific level variable at (0.01). In the light of the results of the research, a number of recommendations and suggestions were presented to enhance the practice of leadership dimensions in the heads of scientific departments at Hafr Al-Batin University and the various Saudi and Arab universities.